Eímerias de los bovinos de Costa Rica. I. Incidencia en animales adultos y sanos - Ruiz, Armando (1959)
Fecal matter from one hundred adult and apparently healthy head of cattle at the Municipal Slaughterhouse, San Jose, Costa Rica, was examined for Eimeria oocysts. Twelve animals were found to be parasitized, the species and incidence being as follows: E. bovis, 7 per cent; E. ellipsoidalis, 3 per cent; E. zürni, 1 per cent; and E. cylindrica, 1 per cent.